Dampak Adanya Generasi Strawberry Terhadap Implementasi Nilai-Nilai Pancasila - Zega, Muhammad Aiman Zikri; Bagas Adhi Nugraha; Banu Arief Muzaki; Ghaisan Daffa Al Fayadh; Muhammad Nashirul Haq Resa; Raden Arya Mucharom Dwi Mahesa; Yayang Furi Furnama Sari (Innovative: Journal Of Social Science Research, 2024)
Abstract Strawberry Generation, as a representation of Generation Z that tends to be individualistic and accustomed to instant convenience, has a significant influence on fundamental values in society such as divinity, humanity, unity, populism, and justice. In terms of divinity, this generation's characteristics of being vulnerable to pressure and lack of mental resilience can affect their perception of spiritual values. While in terms of humanity, despite their individualistic tendencies, this generation also shows commitment to social and environmental issues. However, challenges arise in the context of technology that can reduce the level of empathy and in-person social interaction. In terms of unity, this generation's characteristics of emancipation, empathy and openness play an important role in strengthening social relations and tolerance. However, in terms of populism, the tendency towards individualism can inhibit active participation in deliberation and affect relationships between individuals. As for justice, this generation shows awareness of social justice issues, but is often caught up in negative social media usage. The solution to overcoming the Strawberry Generation phenomenon involves character building through spiritual values, enhancing critical thinking skills, the spirit of mutual cooperation, and cultivating a growth mindset. Thus, this generation has great potential to shape a more inclusive, harmonious and equitable society if given the right guidance and support. Keywords: Strawberry Generation, Character, Values